2012
DOI: 10.1158/1078-0432.ccr-11-1987
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Therapy for Melanoma Patients with KIT Mutations

Abstract: Purpose: Recent studies have shown activating KIT mutations in melanoma originating from mucosa, acral, or cumulative sun-damaged skin sites. We aimed to assess the predictive role of KIT mutation, amplification, or overexpression for response to treatment with the kinase inhibitor sunitinib.Experimental Design: Tumor tissues from 90 patients with stage III or IV acral, mucosal, or cumulative sun-damaged skin melanoma underwent sequencing of KIT, BRAF, NRAS, and GNAQ genes, FISH analysis for KIT amplification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 25 publications
4
103
1
7
Order By: Relevance
“…As a competitive ATP antagonist, sunitinib inhibits the phosphorylation of several tyrosine kinase receptors including VEGFR, PDGFR, and stem cell factor receptor (c-KIT) (1). Sunitinib is approved for treating patients with advanced renal cell carcinoma (2), pancreatic neuroendocrine tumors (3), and gastrointestinal stromal tumors (4,5) and is being tested in other types of cancer including osteosarcoma (6), colorectal cancer (7), and melanoma (8). However, a substantial percentage of patients are intrinsically resistant to sunitinib, and most patients who show initial response to treatment with sunitinib eventually relapse and develop progressive disease secondary to acquired sunitinib resistance, resulting in a modest overall therapeutic benefit (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…As a competitive ATP antagonist, sunitinib inhibits the phosphorylation of several tyrosine kinase receptors including VEGFR, PDGFR, and stem cell factor receptor (c-KIT) (1). Sunitinib is approved for treating patients with advanced renal cell carcinoma (2), pancreatic neuroendocrine tumors (3), and gastrointestinal stromal tumors (4,5) and is being tested in other types of cancer including osteosarcoma (6), colorectal cancer (7), and melanoma (8). However, a substantial percentage of patients are intrinsically resistant to sunitinib, and most patients who show initial response to treatment with sunitinib eventually relapse and develop progressive disease secondary to acquired sunitinib resistance, resulting in a modest overall therapeutic benefit (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The patient experienced a marked reduction in both the size and number of metastatic lesions over a four month treatment period [17]. Minor et al observed a complete remission for 15 months and two partial remissions lasting 1 month and 7 months when using sunitinib to treat mucosal melanomas [18]. No KIT testing was performed on our case report patient, but again, the promise of these therapies indicates that KIT testing should be standard of care for the management of extracutaneous melanomas.…”
Section: Discussionmentioning
confidence: 66%
“…24,25,27,28 Furthermore, the efficacy of these agents in other c-Kit positive tumors is not as evident, especially in SCLC and leukemia (AML) where clinical trials have failed in patients with relapsed or refractory disease, [30][31][32] and in melanoma where modest drug activity was reported predominantly in patients with mutant c-Kit tumors. 33,34 A function blocking antibody is an alternative approach to targeting c-Kit expressing cancers. Previous reports of c-Kit antibodies (e.g., YB5.B8, SR-1), 35,36 lacked extensive in vivo characterization and demonstrated potential for agonistic activity.…”
Section: Discussionmentioning
confidence: 99%
“…44 Similarly, in melanoma there are reports of aberrant c-Kit expression and presence of activating mutations in the acral and mucosal tumor subtypes. 15,23,33,34 The observed in vitro and in vivo sensitivity of c-Kit expressing melanomas to CK6 suggests this is an additional indication for antibody mediated therapy. A more extensive evaluation of c-Kit expression across a broader panel of primary tumor samples is warranted (along with tumor molecular profiling) to identify additional c-Kit positive cancer types eligible for CK6 preclinical efficacy testing which ultimately will provide a better understanding of patient population most suitable to receive and likely benefit from CK6 therapy in the clinic.…”
Section: Discussionmentioning
confidence: 99%